ENHANCEMENT OF PEER COMPANIAN ROLE IN AVOIDING DRUG USAGE THROUGH THE ENTREPRENEURIAL GROUP IN MABAR URBAN VILLAGE, MEDAN DELI SUB-DISTRICT OF MEDAN CITY - Abdul Jalil Amri Arma; Zulfendri (Talenta Publisher, 2018)
Adolescence is an unstable period compared to the next period after it. Consequently, teenagers tend to be trapped in the misleading societies of their future. In addition, technological developments that are increasingly easy to access by teenagers will open up a great opportunity for them to know things, both positive and negative. Therefore, adolescents should be directed as early as possible in order to live productively through an entrepreneurial activity. The purposes are to increase adolescent knowledge about drugs and how to control it, enhance the role of adolescents as peer companions who will be able to influence their friends in avoiding the use of drugs, and formed an entrepreneurial group as an effort to empower teenagers to avoid the dangers of drugs. Form of activities that have been done in this community service are: started with training for teenagers about drugs and its dangers, entrepreneurship, adolescent facilitation that establishes a business group for the same target to produce the products and services that able to increase economic and productivity until finally, the teenager can be independent and protected from drug user interactions. Two motorbike washing groups were formed by name â€œDoorsmer Bahagia Bersamaâ€ for Neighborhood VI and â€œDoorsmer Bersama Bahagiaâ€ for Neighborhood XIX, Mabar Urban Village, Medan Deli Sub-District, Medan City, under the coordination of the Neighborhood Head as a forum for youth associations of Al-Jihad Mosque and Al-Ikhlas Musholla teenagers.